ECONOMIC AND LEGAL ESTIMATION OF INTRODUCTION OF FINANCIAL BILLS IN UKRAINE - L. Hudzynska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article deals with economic and legal estimation of risks the introduction of financial bills in Ukraine.